The Effect of Service Quality on Customer Satisfaction: Case Study from PT. PLN (Persero) Baras District, North Mamuju Regency - A. Albar (Golden Ratio of Data in Summary, 2024)
This study uses questionnaires, interviews, observations, and document reviews to align the respondents' answers with the actual situation to ensure the accuracy of the data obtained. The results will be presented in percentage figures and frequency distribution tables. The analysis reveals that all dimensions of service quality—physical evidence, reliability, responsiveness, assurance, and empathy—are significantly related to customer satisfaction at Perusahaan Listrik Negara (PLN) in Baras District, North Mamuju Regency. Specifically, each dimension, including tangible evidence, empathy, reliability, responsiveness, and assurance, contributes to customer satisfaction. Among these, reliability stands out as the most influential factor, as indicated by its highest Chi-Square (χ²) value, contingency coefficient, and Cramér's V, though physical evidence, responsiveness, assurance, and empathy also play important roles in enhancing overall customer satisfaction.